(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2001)
This paper looks at how phenomenology as a research method can be applied to human phenomena particularly in the therapeutic context. It makes connections between the phenomenological method and existing therapeutic practice. Some suggestions are made about the appropriateness of specific verbal and non verbal interventions